Kesalahan Mahasiswa dalam Pembuktian Matematik - Rezky Agung Herutomo (Didaktik Matematika, 2019)
Proofs are the key component in mathematics and mathematics learning. But in reality, there are still many students who make errors when constructing mathematical proofs. Therefore this study aimed to identify common errors when the students are constructing mathematical proofs. The participant of this study was 51 of 3rd year students of Mathematics Education Department who enrolled in Real Analysis course in the second semester of the 2017/2018 academic year. The data of the study were obtained by conducting a test consisting of five questions and interview guidelines. The errors identified in this study were (1) proving general statements using specific examples, (2) inappropriate algebraic manipulation in mathematical induction, (3) incorrect reasoning and assumptions in proving with contradictions, and (4) reasoning errors involving natural numbers in mathematical induction. Hence, further study can be developed learning models that promote the conceptual understanding, logical reasoning, and mastery of mathematical proof techniques.